Benchmarking User Experience on Mobile Banking Applications in Indonesia: A Comparative Study Using the User Experience Questionnaire - Kadek Yunita Dewi; I Dewa Ayu Indah Saraswati; Yulia Mariasmi Kiuk; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (Universitas Negeri Padang, 2026)
Intense competition in digital banking services demands the optimization of User Experience (UX); however, the UX quality across mobile banking applications has not yet been comprehensively mapped. This study conducts a comparative analysis of mobile banking applications in Indonesia through a preliminary observation using a purposive sampling technique. The evaluation was carried out using the User Experience Questionnaire (UEQ) to measure six UX dimensions, with reliability testing confirming that the instrument was reliable. The results show all applications achieved positive scores across the six UEQ dimensions. BRImo (BRI) ranked highest overall, particularly in the efficiency (2.225) and dependability (2.188) dimensions, BNI Mobile Banking excelled in the novelty dimension, with the highest score (2.088). In addition, BNI Mobile Banking recorded higher efficiency (2.113) and dependability (1.913) scores compared to Livin’ by Mandiri and BCA Mobile. Meanwhile, BCA Mobile outperformed Livin’ by Mandiri in the perspicuity (1.988) and stimulation (1.925) dimensions, whereas Livin’ by Mandiri only surpassed BNI Mobile Banking and BCA Mobile in the attractiveness dimension (1.900). However, the results of the Kruskal–Wallis test indicate that the differences in scores among the applications were not statistically significant. Based on the global UEQ benchmark, all four applications demonstrate very good UX quality, predominantly in the excellent category. BRImo is the only application that achieved the excellent category across all dimensions, while Livin’ by Mandiri obtained two dimensions in the good category, followed by BNI Mobile Banking and BCA Mobile, each with one dimension in the good category.